PERSONAL DATA PROTECTION IN THE ERA OF GLOBALIZATION (INDONESIA PERSPECTIVE) - Rahman, Yogi Muhammad; Haora, Aflah; Sutansi, Elsa Nurfitriani (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
ABSTRACT: This journal explores the topic of securing personal data in the era of globalization, focusing on the legal framework of International Law and existing laws and regulations in Indonesia, especially the provisions stipulated in Law Number 27 of 2022 concerning Data Protection. The main objective of this study is to provide readers with knowledge regarding the personal data protection regulatory landscape at both national and international levels. This research uses juridical-normative and juridical-empirical methodologies to collect, compile, and research research data. This approach includes the study of legal theories and concepts related to the legal principles of laws and regulations, especially those contained in Law Number 27 of 2022, through journal references or legal materials through electronic media. The goal is to gain theoretical insights that can serve as a foundation for research. Furthermore, this research gave birth to a discourse on individual information governance within the framework of global jurisprudence and regulatory framework in Indonesia, especially Law Number 27 of 2022, along with the consequences caused after its implementation.Keywords; Personal Data, Data Protection, the Era of Globalization